2020
DOI: 10.1139/apnm-2020-0272
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour and health in adults: an overview of systematic reviews

Abstract: The purpose of this overview of systematic reviews was to determine the relationship between different types and patterns of sedentary behaviour and selected health outcomes in adults and older adults. Five electronic databases were last searched in May, 2019, with a 10-year search limit. Included reviews met the a priori population (community-dwelling adults aged 18 years and older), intervention/exposure/comparator (various types and/or patterns of sedentary behaviour), and outcomes criteria. Eighteen system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
172
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(182 citation statements)
references
References 60 publications
5
172
0
5
Order By: Relevance
“…Sleep, sedentary behaviour (SED), light intensity physical activity (LIPA), and moderate-to-vigorous intensity physical activity (MVPA) are movement behaviours and time spent in these behaviours adds up to a constant 24h per day sum [1,2]. Short and long sleep durations and greater time spent in SED have been associated with an increased risk of mortality whereas more time spent being physically active has been associated with reduced mortality risk [3][4][5]. Previous studies have largely explored associations between individual movement behaviours and mortality in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep, sedentary behaviour (SED), light intensity physical activity (LIPA), and moderate-to-vigorous intensity physical activity (MVPA) are movement behaviours and time spent in these behaviours adds up to a constant 24h per day sum [1,2]. Short and long sleep durations and greater time spent in SED have been associated with an increased risk of mortality whereas more time spent being physically active has been associated with reduced mortality risk [3][4][5]. Previous studies have largely explored associations between individual movement behaviours and mortality in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in 24-hour movement behaviors may further compound the negative changes reported in mental and physical health during the pandemic. Prior to the COVID-19 epidemic, it was already well documented that 24-hour movement behaviors are associated with physiological and mental health [5][6][7]. Since then, it has been suggested that changes in physical activity due to COVID-19 increase the risk of cardiovascular disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…3 By 2000, estimated global measles mortality was 539 000 deaths per year. 4 Further declines followed the introduction of catch-up vaccination cam paigns to immunise children missed by routine immunisation. Measles cases declined through 2008, and regional elimination targets for measles were established thereafter.…”
Section: Physical Activity Guidelines 2020: Comprehensive and Inclusive Recommendations To Activate Populationsmentioning
confidence: 99%
“…5 In 2016, when measles elimination was verified for the Americas, the global number of reported measles cases reached a low of 132 490. 4 But measles is extremely infectious, with a basic reproduction number of 12−18. 6 At least 95% vaccination coverage is required for herd immunity.…”
Section: Physical Activity Guidelines 2020: Comprehensive and Inclusive Recommendations To Activate Populationsmentioning
confidence: 99%
See 1 more Smart Citation